TEACHING MATHEMATICS FOR HUMANITIES STUDENTS - Yuriy V. Pavlyuchenko (Высшее образование в России)
The article discusses the problems concerning teaching mathematics for Humanities students and considers the contents of a textbook on Mathematics for Humanities students. By the way the basic principles and the main education conceptions (as authors see them) of Mathematics teaching for non-Math students are discussed.